Educating for Identity: Problematizing and Deconstructing Our Literacy Pasts - Parr, Michelann; Campbell, Terry A. (Alberta Journal of Educational Research, 2011)
In order to become effective teachers of language and literacy, it is critical for teacher candidates to have a sense of who they are as literate beings, how their literacy pasts have been lived, and how this might have an influence on the students in their classrooms. As teacher educators, we should not allow teacher candidates to rest simply with the recollection of key literacy events and memories. In order to be fully aware and wide awake to the complex task of teaching language and literacy, teacher candidates need to be engaged in active discussion that involves problematizing and unpacking their experiences, memories, and stories and what they really mean in past and present conceptualizations of literacy and sociocultural contexts. Pour devenir des enseignants de langue et de littératie, il est critique que les stagiaires aient un sens d’eux-mêmes comme êtres lettrés, qu’ils soient conscients de leur passé en matière de littératie, et qu’ils aient une idée de l’influence de ces facteurs sur leurs élèves en salle de classe. En tant que formateurs d’enseignants, nous ne devrions pas permettre aux stagiaires de se limiter à des souvenirs portant sur des événements relatifs à la littératie. Afin d’être pleinement conscients et éveillés face à la tâche complexe qu’est celle d’enseigner la langue et la littératie, les stagiaires doivent prendre part à des discussions actives, problématisant et déballant leurs expériences, leurs souvenirs et leurs récits personnels, et analysant leur sens selon les conceptualisations du passé et du présent de la littératie et en fonction des contextes socioculturels.